Low-humidity sensor taking polyion liquid film based on discontinuous conductive polymer template as sensitive layer and preparation method of low-humidity sensor
By adopting a combination of polyion liquid film based on discontinuous conductive polymer templates and graphite carbon interdigital electrodes in low-humidity sensors, the impedance value of the sensor and the sensitivity are improved, and the impedance of low-humidity detection in the prior art is solved The problems of high value and detection limit achieve fast and accurate monitoring of low-humidity environments.
Patent Information
- Application Number
- CN202411498876.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-10
AI Technical Summary
The existing polyion liquid-based low humidity sensors have low ion conductivity in low humidity environments, resulting in high impedance value and high detection limits and low sensitivity, making it difficult to meet the needs of fast, sensitive and precise monitoring of low humidity environments.
The polyionic liquid film based on discontinuous conductive polymer template is used as the sensitive layer, and the pre-aggregated methanol dispersed conductive polymer material is prepared by oxidative polymerization and solvent exchange method, and the "ene-thioxide click chemical reaction" excitated by ultraviolet light Prepare polyion liquid films in situ, combined with graphite carbon interdigital electrodes to reduce the impedance value of the sensor and improve sensitivity.
It realizes low impedance value and high sensitivity, is suitable for humidity detection in the low humidity range, has small humidity hysteresis and high stability, and is suitable for industrial mass production, solving the high impedance value and high impedance value of traditional polymer-based humidity sensors in low humidity detection. Detection height limit problem.
Smart Images

Figure CN119290977A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of humidity sensors, and in particular relates to a low humidity sensor using a polyionic liquid film with a discontinuous conductive polymer template as a sensitive layer and a preparation method thereof. Background Art
[0002] Humidity, as the main parameter to measure the dryness and wetness of air, is closely related to human production and life. Low humidity environment monitoring is widely used in industrial production, agricultural planting, grain storage, aerospace, medical and health care and other fields. With the development of science and technology and industrial manufacturing, rapid, sensitive and accurate monitoring of low humidity environments is particularly important.
[0003] There are many methods used to detect low humidity, including spectroscopy, gravimetric method, and cold mirror dew point method. These methods are widely used in the laboratory for accurate detection of low humidity and calibration of humidity standards, but these methods have problems such as long time consumption, high cost, and complex operation. Impedance humidity sensors have the advantages of simple preparation, low cost, and small size, and are a technology with great application prospects in the field of low humidity detection. At present, polyionic liquid materials, as a polymer material with ionic liquid properties, are widely used in low humidity sensors. However, as a polymer material, polyionic liquids have the disadvantage of low ionic conductivity in low humidity environments, resulting in polyionic liquid-based impedance-type low humidity sensors having high impedance values and high detection limits in low humidity detection. Therefore, designing a new polyionic liquid-based sensitive membrane, reducing the impedance value of polyionic liquid-based impedance-type low humidity sensors, improving the sensitivity of low humidity sensors, and reducing the detection limit of low humidity sensors without changing the characteristics of polyionic liquids, is of great significance for obtaining low humidity sensors with excellent performance. Summary of the invention
[0004] The object of the present invention is to provide a low humidity (5% to 35% relative humidity) sensor with a polyionic liquid film having a discontinuous conductive polymer template as a sensitive layer and a preparation method thereof, wherein the sensor has a low impedance value and high sensitivity.
[0005] The invention discloses a low humidity sensor with a polyionic liquid film based on a discontinuous conductive polymer template as a sensitive layer, comprising a ceramic substrate with 2 to 5 pairs of graphite carbon interdigital electrodes on the surface, and a temperature sensitive layer (thickness 10 to 100 μm) drop-coated on the ceramic substrate and the graphite carbon interdigital electrodes; the graphite carbon interdigital electrodes are 5 to 10 mm long, 3 to 7 mm wide, 0.2 to 1.0 mm thick, with an electrode spacing of 0.2 to 1.0 mm, and the number of electrode pairs is 2 to 5 pairs; wherein the temperature sensitive layer is a polyionic liquid film based on a discontinuous conductive polymer template, and the invention firstly adopts an oxidative polymerization method and a solvent exchange method to prepare a pre-agglomerated methanol-dispersed conductive polymer material, prepares a discontinuous conductive polymer template on the substrate surface after drying and annealing, and then in-situ prepares a polyionic liquid film on the discontinuous conductive polymer template by an "ene-thiol click chemical reaction" under ultraviolet light excitation.
[0006] The low humidity sensor described in the present invention is an impedance-type humidity sensor, and the output signals between its interdigital electrodes are all impedance signals, which are obtained by impedance analyzer testing. The humidity sensitive layer on the surface of the graphite carbon interdigital electrode will adsorb water molecules after contacting water molecules in the air, and the impedance value of the humidity sensitive layer will change. By comparing the change in the impedance value of the humidity sensitive layer on the surface of the interdigital electrode measured by the impedance analyzer before and after the low humidity sensor absorbs moisture, the sensitivity of the sensor can be obtained (test voltage: the voltage applied to both ends of the interdigital electrode is 1V, 1000Hz AC voltage). The sensitivity is calculated by dividing the difference between the impedance value of the sensor in the initial relative humidity (5%) test environment and its impedance value in the highest relative humidity (35%) test environment by its impedance value in the highest relative humidity (35%) test environment. Hysteresis is the maximum relative humidity difference at the same impedance value between the adsorption sensitivity curve of the humidity sensor at 5% to 35% relative humidity and the desorption sensitivity curve at 35% to 5% relative humidity, which is drawn by the test relationship between relative humidity and impedance value. The response time refers to the time it takes for the impedance value of the humidity sensor to decrease by 90% after being placed in an environment of 33% relative humidity from an environment of 7% relative humidity. The recovery time refers to the time it takes for the impedance value of the humidity sensor to increase by 90% after being placed in an environment of 7% relative humidity from an environment of 33% relative humidity.
[0007] A method for preparing a low humidity sensor using a polyionic liquid film with a discontinuous conductive polymer template as a sensitive layer, the steps of which are as follows (unless otherwise specified, the solutions described in the present invention are all methanol solutions):
[0008] (1) dissolving 0.35-0.40 mmol of 3,4-ethylenedioxythiophene and 0.70-0.80 mmol of a perfluorosulfonic acid ion resin aqueous solution in 7.5-9.0 mL of water to prepare a mixed solution;
[0009] (2) stirring the mixed solution obtained in step (1) for 1.5 to 3.0 hours, and then sonicating for 8 to 15 minutes to form an emulsion;
[0010] (3) adding 120-122 mg of ferric chloride to the emulsion obtained in step (2) to form a mixed solution;
[0011] (4) subjecting the mixed solution obtained in step (3) to a polymerization reaction at 20 to 25° C. for 40 to 60 hours to obtain an aqueous dispersion of the conductive polymer;
[0012] (5) purifying the conductive polymer aqueous dispersion obtained in step (4) using a 500 Da semipermeable membrane to remove unreacted ferric chloride and 3,4-ethylenedioxythiophene to obtain a dark blue conductive polymer aqueous dispersion;
[0013] (6) subjecting the dark blue conductive polymer aqueous dispersion obtained in step (5) to a centrifugal treatment at 8000 to 12000 rad / min for 20 to 40 min to separate the dark blue conductive polymer;
[0014] (7) adding 8.5 to 12.5 mL of methanol solvent to the dark blue conductive polymer obtained in step (6), and sonicating for 1.5 to 3.0 h until it is completely dispersed;
[0015] (8) repeating steps (6) and (7) for 2 to 4 times to obtain a dark blue pre-agglomerated conductive polymer methanol dispersion having a solid content of 1.2 to 1.5 wt %;
[0016] (9) dissolving 65-75 mg of an ionic liquid in a methanol solvent to prepare a 90-110 mg / mL ionic liquid solution, wherein the ionic liquid is 1-allyl-3-vinylimidazolium chloride;
[0017] (10) subjecting the ionic liquid solution obtained in step (9) to ultrasonic treatment for 2 to 5 minutes to obtain a uniformly dispersed ionic liquid solution;
[0018] (11) adding 95 to 105 mg of a polymerization monomer to the ionic liquid solution obtained in step (10), wherein the polymerization monomer is pentaerythritol tetrakis-3-mercaptopropionate;
[0019] (12) adding methanol solvent to the solution obtained in step (11), wherein the total amount of methanol solvent in step (9) and step (12) is 900 to 1100 μL, and ultrasonicating the solution for 2 to 5 minutes to obtain a uniformly dispersed mixture solution;
[0020] (13) adding 1.5 to 2.5 mg of an ultraviolet light curing initiator to the mixture solution obtained in step (12), wherein the ultraviolet light curing initiator is benzoin dimethyl ether, to obtain a polyionic liquid precursor solution;
[0021] (14) subjecting the polyionic liquid precursor solution obtained in step (13) to ultrasonic treatment for 2 to 5 minutes to obtain a uniformly dispersed polyionic liquid precursor solution;
[0022] (15) Pipette 1-3 μL of the dark blue pre-agglomerated conductive polymer methanol dispersion obtained in step (8) and drop-coat it on a ceramic substrate having 2-5 pairs of graphite carbon interdigital electrodes on the surface, dry it at 50-70° C. for 25-35 min, and then anneal it at 110-130° C. for 8-12 min;
[0023] (16) Pipette 1 to 3 μL of the uniformly dispersed polyionic liquid precursor solution obtained in step (14) and drop-coat it onto the surface of the device obtained in step (15);
[0024] (17) placing the device obtained in step (16) in a CL-1000 UV crosslinking irradiator and irradiating with 365 nm UV light for 20 to 40 min;
[0025] (18) The device obtained in step (17) is aged at a relative humidity of 65-85% for 1-12 hours to obtain an impedance-type low-humidity sensor based on a polyionic liquid film with a discontinuous conductive polymer template as a sensitive layer.
[0026] The advantages of the present invention are:
[0027] 1) The raw materials and the ceramic substrate with graphite carbon interdigital electrodes of the present invention can be purchased from the market, with low raw material cost, high yield, good structural consistency, and suitable for mass production;
[0028] 2) The low humidity sensor prepared by the present invention has a simple manufacturing process and a small size, and is suitable for industrial batch production;
[0029] 3) The low humidity sensor prepared by the present invention has excellent humidity-sensitive properties in the low humidity range, including high sensitivity (224.0), small humidity hysteresis (0.5% relative humidity) and high stability, and has low impedance value (<30MΩ) and low detection limit (<1% relative humidity), which solves the problems of high impedance value, high detection limit and low sensitivity of most polymer-based humidity sensors when detecting low humidity;
[0030] 4) The present invention utilizes the property that the polymer material is closely connected with the conductive polymer in an environment containing water, so that the obtained polyionic liquid film based on the discontinuous conductive polymer template has strong stability;
[0031] 5) The present invention utilizes the special ionic ligand configuration of the conductive polymer material. When in contact with the polycationic polyionic liquid, the polyanionic skeleton structure of the counter-ionic ligand of the conductive polymer material inhibits the movement of anions between the two components. By using this special structure, an ion / electron mixed conductive configuration is formed in the polyionic liquid membrane. By introducing conductive polymers between the polyionic liquids, the impedance value of the polyionic liquid-based low humidity sensor is successfully reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is the infrared absorption spectra of the polyionic liquid prepared in Comparative Example 1 and the conductive polymer material prepared in Comparative Example 2;
[0033] Figure 2 is a frequency characteristic curve of the impedance-type low humidity sensor based on the polyionic liquid film with a discontinuous conductive polymer template prepared in Example 2 under low humidity;
[0034] Figure 3 The humidity sensitivity characteristic curves of the impedance-type low humidity sensor based on the polyionic liquid film with a discontinuous conductive polymer template prepared in Comparative Example 1, Comparative Example 2 and Examples 1 to 3 at a relative humidity of 5% to 35%;
[0035] Figure 4 is a hysteresis curve of the impedance-type low humidity sensor based on the polyionic liquid film with a discontinuous conductive polymer template prepared in Example 2 at a relative humidity of 5% to 35%;
[0036] Figure 5 Response recovery curves of the impedance-type low humidity sensor based on the polyionic liquid film with a discontinuous conductive polymer template prepared in Example 2 at 7% relative humidity and 33% relative humidity;
[0037] Figure 6 It is a multiple measurement repeatability curve of the impedance-type low humidity sensor based on the polyionic liquid film with a discontinuous conductive polymer template prepared in Example 2 at 7% relative humidity and 33% relative humidity;
[0038] Figure 7 This is a 35-day long-term stability test of the impedance-type low-humidity sensor based on the polyionic liquid film with a discontinuous conductive polymer template prepared in Example 2 at a relative humidity of 5% to 35%. DETAILED DESCRIPTION
[0039] Comparative Example 1
[0040] (1) dissolving 69.7 mg of an ionic liquid in a methanol solvent to prepare a 100 mg / mL ionic liquid solution, wherein the ionic liquid is 1-allyl-3-vinylimidazolium chloride;
[0041] (2) subjecting the solution obtained in step (1) to ultrasonic treatment for 5 minutes to obtain a uniformly dispersed ionic liquid solution;
[0042] (3) adding 100 mg of a polymerization monomer to the solution of step (2), wherein the polymerization monomer is pentaerythritol tetrakis-3-mercaptopropionate;
[0043] (4) adding methanol solvent to the solution obtained in step (3), wherein the total amount of methanol solvent in step (1) and step (4) is 1000 μL, and ultrasonicating the solution for 5 min to obtain a uniformly dispersed mixture solution;
[0044] (5) adding 2.1 mg of an ultraviolet light curing initiator to the mixed solution of step (4), wherein the ultraviolet light curing initiator is benzoin dimethyl ether, to obtain a polyionic liquid precursor solution;
[0045] (6) subjecting the polyionic liquid precursor solution obtained in step (5) to ultrasonic treatment for 5 minutes to obtain a uniformly dispersed precursor solution;
[0046] (7) taking 2 μL of the uniformly dispersed polyionic liquid precursor solution obtained in step (6), and drop-coating it on a ceramic substrate having three pairs of graphite carbon interdigital electrodes on its surface;
[0047] (8) placing the device obtained in step (7) in a CL-1000 UV crosslinking irradiator and irradiating with 365 nm UV light for 30 min;
[0048] (9) The device obtained in step (8) is aged at 75% relative humidity for 12 hours to obtain an impedance-type low-humidity sensor based on a polyionic liquid film; the thickness of the sensitive layer is 50 μm, the length of the graphite carbon interdigital electrode is 8 mm, the width is 5 mm, the thickness is 0.6 mm, and the electrode spacing is 0.6 mm.
[0049] Comparative Example 2
[0050] (1) dissolving 0.375 mmol of 3,4-ethylenedioxythiophene and 0.750 mmol of a perfluorosulfonic acid ion resin aqueous solution in 8 mL of water to prepare a mixed solution;
[0051] (2) stirring the mixed solution obtained in step (1) for 2 h, and then sonicating for 10 min to form an emulsion;
[0052] (3) adding 121 mg of ferric chloride to the emulsion obtained in step (2) to form a mixed solution;
[0053] (4) subjecting the mixed solution obtained in step (3) to a polymerization reaction at 25° C. for 48 hours to obtain an aqueous dispersion of a conductive polymer;
[0054] (5) purifying the conductive polymer aqueous dispersion obtained in step (4) using a 500 Da semipermeable membrane to remove unreacted ferric chloride and 3,4-ethylenedioxythiophene to obtain a dark blue conductive polymer aqueous dispersion;
[0055] (6) centrifuging the dark blue conductive polymer aqueous dispersion obtained in step (5) at 10,000 rad / min for 30 min to separate the dark blue conductive polymer;
[0056] (7) adding 10 mL of methanol solvent to the dark blue conductive polymer obtained in step (6) and ultrasonicating for 2 h until it is completely dispersed;
[0057] (8) repeating step (6) and step (7) three times to obtain a dark blue pre-agglomerated conductive polymer methanol dispersion with a solid content of 1.3 wt %;
[0058] (9) Pipette 2 μL of the dark blue pre-agglomerated conductive polymer methanol dispersion obtained in step (8) and drop-coat it on a ceramic substrate with three pairs of graphite carbon interdigital electrodes on the surface, dry it at 60° C. for 30 min, and then anneal it at 120° C. for 10 min;
[0059] (10) The device obtained in step (9) is aged at 75% relative humidity for 12 hours to obtain an impedance-type low-humidity sensor based on a discontinuous conductive polymer template, wherein the graphite carbon interdigital electrode has a length of 8 mm, a width of 5 mm, a thickness of 0.6 mm, and an electrode spacing of 0.6 mm.
[0060] Example 1
[0061] (1) dissolving 0.375 mmol of 3,4-ethylenedioxythiophene and 0.750 mmol of a perfluorosulfonic acid ion resin aqueous solution in 8 mL of water to prepare a mixed solution;
[0062] (2) stirring the mixed solution obtained in step (1) for 2 h, and then ultrasonicating for 10 min to form an emulsion;
[0063] (3) adding 121 mg of ferric chloride to the emulsion obtained in step (2) to form a mixed solution;
[0064] (4) subjecting the mixed solution obtained in step (3) to a polymerization reaction at 25° C. for 48 hours to obtain an aqueous dispersion of a conductive polymer;
[0065] (5) purifying the conductive polymer aqueous dispersion obtained in step (4) using a 500 Da semipermeable membrane to remove unreacted ferric chloride and 3,4-ethylenedioxythiophene to obtain a dark blue conductive polymer aqueous dispersion;
[0066] (6) centrifuging the dark blue conductive polymer aqueous dispersion obtained in step (5) at 10,000 rad / min for 30 min to separate the dark blue conductive polymer;
[0067] (7) adding 10 mL of methanol solvent to the dark blue conductive polymer obtained in step (6) and ultrasonicating for 2 h until it is completely dispersed;
[0068] (8) repeating step (6) and step (7) three times to obtain a dark blue pre-agglomerated conductive polymer methanol dispersion with a solid content of 1.3 wt %;
[0069] (9) dissolving 69.7 mg of ionic liquid in methanol solvent to prepare a 100 mg / mL ionic liquid solution, wherein the ionic liquid is 1-allyl-3-vinylimidazolium chloride;
[0070] (10) subjecting the solution obtained in step (9) to ultrasonic treatment for 5 minutes to obtain a uniformly dispersed ionic liquid solution;
[0071] (11) adding 100 mg of a polymerization monomer to the solution of step (10), wherein the polymerization monomer is pentaerythritol tetrakis-3-mercaptopropionate;
[0072] (12) adding methanol solvent to the solution obtained in step (11), wherein the total amount of methanol solvent used in step (9) and step (12) is 1000 μL, and ultrasonicating the solution for 5 min to obtain a uniformly dispersed mixture solution;
[0073] (13) adding 2.1 mg of an ultraviolet light curing initiator to the mixed solution of step (12), wherein the ultraviolet light curing initiator is benzoin dimethyl ether, to obtain a polyionic liquid precursor solution;
[0074] (14) subjecting the polyionic liquid precursor solution obtained in step (13) to ultrasonic treatment for 5 minutes to obtain a uniformly dispersed precursor solution;
[0075] (15) Pipette 1 μL of the dark blue pre-agglomerated conductive polymer methanol dispersion obtained in step (8) and drop-coat it on a ceramic substrate with three pairs of graphite carbon interdigital electrodes on the surface, dry it at 60°C for 30 min, and then anneal it at 120°C for 10 min;
[0076] (16) Pipette 2 μL of the uniformly dispersed polyionic liquid precursor solution obtained in step (14) and drop-coat it onto the surface of the device obtained in step (15);
[0077] (17) placing the device obtained in step (16) in a CL-1000 UV crosslinking irradiator and irradiating with 365 nm UV light for 30 min;
[0078] (18) The device obtained in step (17) is aged at 75% relative humidity for 12 hours to obtain an impedance-type low-humidity sensor based on a polyionic liquid film with a discontinuous conductive polymer template, wherein the thickness of the sensitive layer is 50 μm, the length of the graphite carbon interdigital electrode is 8 mm, the width is 5 mm, the thickness is 0.6 mm, and the electrode spacing is 0.6 mm.
[0079] Example 2
[0080] Steps (1) to (14) are the same as those in Example 1;
[0081] (15) Pipette 2 μL of the dark blue pre-agglomerated conductive polymer methanol dispersion obtained in step (8) and drop-coat it on a ceramic substrate with three pairs of graphite carbon interdigital electrodes on the surface, dry it at 60°C for 30 min, and then anneal it at 120°C for 10 min;
[0082] (16) Pipette 2 μL of the uniformly dispersed polyionic liquid precursor solution obtained in step (14) and drop-coat it onto the surface of the device obtained in step (15);
[0083] (17) placing the device obtained in step (16) in a CL-1000 UV crosslinking irradiator and irradiating with 365 nm UV light for 30 min;
[0084] (18) The device obtained in step (17) is aged at 75% relative humidity for 12 hours to obtain an impedance-type low-humidity sensor based on a polyionic liquid film with a discontinuous conductive polymer template, wherein the thickness of the sensitive layer is 50 μm, the length of the graphite carbon interdigital electrode is 8 mm, the width is 5 mm, the thickness is 0.6 mm, and the electrode spacing is 0.6 mm.
[0085] Example 3
[0086] Steps (1) to (14) are the same as those in Example 1;
[0087] (15) Pipette 3 μL of the dark blue pre-agglomerated conductive polymer methanol dispersion obtained in step (8) and drop-coat it on a ceramic substrate with three pairs of graphite carbon interdigital electrodes on the surface, dry it at 60°C for 30 min, and then anneal it at 120°C for 10 min;
[0088] (16) Pipette 2 μL of the uniformly dispersed polyionic liquid precursor solution obtained in step (14) and drop-coat it onto the surface of the device obtained in step (15);
[0089] (17) placing the device obtained in step (16) in a CL-1000 UV crosslinking irradiator and irradiating with 365 nm UV light for 30 min;
[0090] (18) The device obtained in step (17) is aged at 75% relative humidity for 12 hours to obtain an impedance-type low-humidity sensor based on a polyionic liquid film with a discontinuous conductive polymer template, wherein the thickness of the sensitive layer is 50 μm, the length of the graphite carbon interdigital electrode is 8 mm, the width is 5 mm, the thickness is 0.6 mm, and the electrode spacing is 0.6 mm.
[0091] The Fourier infrared spectra of the polyionic liquid prepared in Comparative Example 1 and the conductive polymer material prepared in Comparative Example 2 are as follows: Figure 1 The characteristic peak of thiol appears at 2950cm -1 、640cm -1 and 982cm -1 The skeleton vibration peak and stretching vibration peak of the imidazole ring appear at 1566 cm -1 and 1172cm -1 The successful synthesis of polyionic liquid materials was proved; the characteristic peak of carbon-carbon double bond is at 1650cm -1 The characteristic peak of sulfur-oxygen double bond appears at 1054 cm -1 The characteristic peak of sulfur-oxygen single bond is 1230 cm -1 , 1156cm -1 The peak at is the characteristic peak of carbon-fluorine bond, indicating that the conductive polymer material has been successfully prepared.
[0092] The frequency characteristic curve of the impedance-type low humidity sensor based on the polyionic liquid film with a discontinuous conductive polymer template prepared in Example 2 in the relative humidity range of 5 to 35% is as follows: Figure 2 As shown. Figure 2 In the present study, for the impedance-type low humidity sensor based on polyionic liquid film with discontinuous conductive polymer template, when the test frequency exceeds 10kHz, the sensitivity is less than 100; when the test frequency is lower than 100Hz, the sensor impedance value is unstable, so 1kHz is selected as the optimal operating frequency.
[0093] The humidity sensitivity characteristic curves of the impedance-type low humidity sensors based on polyionic liquid materials containing hydrophobic components prepared in Comparative Example 1, Comparative Example 2 and Examples 1 to 3 in the relative humidity range of 5 to 35% are as follows: Figure 3As shown. By calculation, the sensitivities of Comparative Example 1 and Comparative Example 2 in the relative humidity range of 5-35% are 150.8 and 0.5, and the sensitivities of Examples 1-3 in the relative humidity range of 5-35% are 276.1, 224.0 and 204.5. The high impedance value and low sensitivity presented in Comparative Example 2 prove the successful preparation of the discontinuous conductive polymer template. The impedance values of Examples 1-3 have been significantly reduced compared with Comparative Example 1, and have higher sensitivity in the relative humidity range of 5-35%; at the same time, with the increase of the conductive polymer content, the impedance value of the low humidity sensor has a downward trend, which proves that the introduction of the polyionic liquid film structure based on the discontinuous conductive polymer template successfully reduces the impedance value of the polyionic liquid-based impedance-type low humidity sensor, while improving the sensitivity.
[0094] The hysteresis curve of the impedance-type low humidity sensor based on the polyionic liquid film with a discontinuous conductive polymer template prepared in Example 2 in the relative humidity range of 5 to 35% is as follows: Figure 4 It can be seen that the hysteresis of the low humidity sensor is very small in the relative humidity range of 5-35%, which is 0.5% relative humidity.
[0095] The response recovery curve of the impedance-type low humidity sensor based on the polyionic liquid film with a discontinuous conductive polymer template prepared in Example 2 between 7% and 33% relative humidity is shown in FIG. Figure 5 The response and recovery time of the sensor in the test are 8 seconds and 63 seconds respectively, which further illustrates that the impedance-type low humidity sensor based on polyionic liquid materials containing hydrophobic components has good response recovery characteristics in low humidity measurement.
[0096] The multiple response recovery curves of the impedance-type low humidity sensor based on the polyionic liquid film with a discontinuous conductive polymer template prepared in Example 2 between 7% and 33% relative humidity are shown in FIG. Figure 6 The sensitivity of the sensor did not change significantly in 5 cycle tests, and the impedance value of the low humidity sensor at 7% relative humidity did not change significantly in multiple tests, which further illustrates that the impedance-type low humidity sensor based on the polyionic liquid film with a discontinuous conductive polymer template has good stability in low humidity measurement.
[0097] The long-term stability test of the impedance-type low humidity sensor based on the polyionic liquid film with a discontinuous conductive polymer template prepared in Example 2 in the range of 5 to 35% relative humidity for 35 days is as follows: Figure 7 During the test, the impedance value of the sensor at the same relative humidity did not change much, proving that the impedance-type low humidity sensor based on the polyionic liquid film with a discontinuous conductive polymer template has good long-term stability.
Claims
1. A method for preparing a low humidity sensor using a polyionic liquid film with a discontinuous conductive polymer template as a sensitive layer, the steps of which are as follows: (1) dissolving 0.35-0.40 mmol of 3,4-ethylenedioxythiophene and 0.70-0.80 mmol of a perfluorosulfonic acid ion resin aqueous solution in 7.5-9.0 mL of water to prepare a mixed solution; (2) stirring the mixed solution obtained in step (1) for 1.5 to 3.0 hours, and then sonicating for 8 to 15 minutes to form an emulsion; (3) adding 120-122 mg of ferric chloride to the emulsion obtained in step (2) to form a mixed solution; (4) subjecting the mixed solution obtained in step (3) to a polymerization reaction at 20 to 25° C. for 40 to 60 hours to obtain an aqueous dispersion of the conductive polymer; (5) purifying the conductive polymer aqueous dispersion obtained in step (4) using a 500 Da semipermeable membrane to remove unreacted ferric chloride and 3,4-ethylenedioxythiophene to obtain a dark blue conductive polymer aqueous dispersion; (6) subjecting the dark blue conductive polymer aqueous dispersion obtained in step (5) to a centrifugal treatment at 8000 to 12000 rad / min for 20 to 40 min to separate the dark blue conductive polymer; (7) adding 8.5 to 12.5 mL of methanol solvent to the dark blue conductive polymer obtained in step (6), and ultrasonicating for 1.5 to 3.0 h until it is completely dispersed; (8) repeating steps (6) and (7) for 2 to 4 times to obtain a dark blue pre-agglomerated conductive polymer methanol dispersion having a solid content of 1.2 to 1.5 wt %; (9) dissolving 65-75 mg of an ionic liquid in a methanol solvent to prepare a 90-110 mg / mL ionic liquid solution, wherein the ionic liquid is 1-allyl-3-vinylimidazolium chloride; (10) subjecting the ionic liquid solution obtained in step (9) to ultrasonic treatment for 2 to 5 minutes to obtain a uniformly dispersed ionic liquid solution; (11) adding 95 to 105 mg of a polymerization monomer to the ionic liquid solution obtained in step (10), wherein the polymerization monomer is pentaerythritol tetrakis-3-mercaptopropionate; (12) adding methanol solvent to the solution obtained in step (11), wherein the total amount of methanol solvent in step (9) and step (12) is 900 to 1100 μL, and ultrasonicating the solution for 2 to 5 minutes to obtain a uniformly dispersed mixture solution; (13) adding 1.5 to 2.5 mg of an ultraviolet light curing initiator to the mixture solution obtained in step (12), wherein the ultraviolet light curing initiator is benzoin dimethyl ether, to obtain a polyionic liquid precursor solution; (14) subjecting the polyionic liquid precursor solution obtained in step (13) to ultrasonic treatment for 2 to 5 minutes to obtain a uniformly dispersed polyionic liquid precursor solution; (15) Pipette 1-3 μL of the dark blue pre-agglomerated conductive polymer methanol dispersion obtained in step (8) and drop-coat it on a ceramic substrate having 2-5 pairs of graphite carbon interdigital electrodes on the surface, dry it at 50-70° C. for 25-35 min, and then anneal it at 110-130° C. for 8-12 min; (16) Pipette 1 to 3 μL of the uniformly dispersed polyionic liquid precursor solution obtained in step (14) and drop-coat it onto the surface of the device obtained in step (15); (17) placing the device obtained in step (16) in a CL-1000 UV crosslinking irradiator and irradiating with 365 nm UV light for 20 to 40 min; (18) The device obtained in step (17) is aged at a relative humidity of 65-85% for 1-12 hours to obtain an impedance-type low-humidity sensor based on a polyionic liquid film with a discontinuous conductive polymer template as a sensitive layer.
2. The method for preparing a low humidity sensor using a polyionic liquid film having a discontinuous conductive polymer template as a sensitive layer as claimed in claim 1, characterized in that: The length of the graphite carbon interdigital electrode is 5 to 10 mm, the width is 3 to 7 mm, the thickness is 0.2 to 1.0 mm, the electrode spacing is 0.2 to 1.0 mm, and the number of electrode pairs is 2 to 5 pairs.
3. The method for preparing a low humidity sensor using a polyionic liquid film having a discontinuous conductive polymer template as a sensitive layer as claimed in claim 1, characterized in that: The thickness of the sensitive layer is 10 to 100 μm.
4. A low humidity sensor with a polyionic liquid film having a discontinuous conductive polymer template as a sensitive layer, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 3.